Author Correction: Promoter interactome of human embryonic stem cell-derived cardiomyocytes connects GWAS regions to cardiac gene networks. Issue 1 (December 2018) - Choy, Mun-Kit; Javierre, Biola; Williams, Simon; Baross, Stephanie; Liu, Yingjuan; Wingett, Steven; Akbarov, Artur; Wallace, Chris; Freire-Pritchett, Paula; Rugg-Gunn, Peter; Spivakov, Mikhail; Fraser, Peter; et al.
In the original version of the Article, the gene symbol for tissue factor pathway inhibitor was inadvertently given as 'TFP1 ' instead of 'TFPI '. This has now been corrected in both the PDF and HTML versions of the Article.